Faktor-Faktor Yang Mempengaruhi Terjadinya Permasalahan Pada Ekonomi Makro Islam Di Indonesia - Muhammad Mustaghfirin; Dewi Ratih; Anugrahi Putri Ziyadatin Ilmi; Eny Lathifah (Universitas 45 Surabaya, 2024)
Macroeconomic problems are complex and multifaceted issues whose causes include several factors. The main focus of this research is on the factors that cause macroeconomic problems both from an internal and external perspective. Internal factors include national income, fiscal policy, poverty, and inflation. Low national income can hamper economic growth and worsen social welfare. Ineffective fiscal policy can result in budget imbalances and waste of resources. Widespread poverty can reduce people's purchasing power and increase social instability. High inflation can erode the value of the currency and people's purchasing power, thereby worsening economic conditions. Meanwhile, external factors that influence the macro economy include international trade and foreign exchange rates. Unbalanced international trade can lead to trade deficits and dependence on imports.